Two new Meitingsunes species (Acari: Syringophilidae) from Indonesian doves (Columbiformes: Columbidae) - Kaszewska, Katarzyna; Skoracki, Maciej; Kavetska, Katarzyna (Zootaxa, 2016)
We describe two new quill mite species of the genus Meitingsunes Glowska and Skoracki, 2010 (Acari: Prostigmata: Syringophilidae) parasitizing columbiform birds (Columbiformes: Columbidae): M. chalcophaps sp. nov. collected from the Emerald Dove, Chalcophaps indica (Linnaeus) and M. turacoenas sp. nov. from the White-faced Cuckoo Dove, Turacoena manadensis (Quoy and Gaimard) (type host) and the Black Cuckoo-Dove, Turacoena modesta (Temminck). All host species were collected in Indonesia. These represent two new genus-level host records for Meitingsunes. In addition, we summarize the diversity of Meitingsunes and present a key to species in this genus.